The Low Rate Telemetry Transmission Simulator - Spacek, Jiri; Kasal, Miroslav (Společnost pro radioelektronické inženýrství, 2007)
The presented paper is dedicated to the low rate telemetry transmission simulator. The basic concept of the system uses the carrier (DSB) and subcarrier (BPSK). The research is focused on the AWGN and carrier phase noise influence. Presented system can be extended with the described carrier phase noise model. In this paper, some issues related to the described model are also discussed. For example, the relation between bit error rate for uncoded bit stream and bit stream with differential coding, which is used in the model. Authors prove the using of Costas loops for very low energy per bit to noise power spectral density ratio. The influence of additive white Gaussian noise and phase noise is also investigated.
Keywords: Low rate telemetry; Simulink® model; BPSK/DSB modulation; phase noise model; noise effect